2021
DOI: 10.1186/s13321-020-00479-8
|View full text |Cite
|
Sign up to set email alerts
|

Could graph neural networks learn better molecular representation for drug discovery? A comparison study of descriptor-based and graph-based models

Abstract: Graph neural networks (GNN) has been considered as an attractive modelling method for molecular property prediction, and numerous studies have shown that GNN could yield more promising results than traditional descriptor-based methods. In this study, based on 11 public datasets covering various property endpoints, the predictive capacity and computational efficiency of the prediction models developed by eight machine learning (ML) algorithms, including four descriptor-based models (SVM, XGBoost, RF and DNN) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
331
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 403 publications
(357 citation statements)
references
References 60 publications
26
331
0
Order By: Relevance
“…This was similar to the previous study where increasing the weights within the neural network architecture did not always improve prediction accuracy [20]. Moreover, it is important to search for a model architecture with the minimum number of weights and the highest prediction accuracy, because the use of an excessive number of weights in the model could induce false positives in prediction outcomes [17]. In QSAR modeling, datasets were collected from a wide range of studies in which experimental values were measured using different experimental protocols.…”
Section: Model Prediction Accuracysupporting
confidence: 86%
See 4 more Smart Citations
“…This was similar to the previous study where increasing the weights within the neural network architecture did not always improve prediction accuracy [20]. Moreover, it is important to search for a model architecture with the minimum number of weights and the highest prediction accuracy, because the use of an excessive number of weights in the model could induce false positives in prediction outcomes [17]. In QSAR modeling, datasets were collected from a wide range of studies in which experimental values were measured using different experimental protocols.…”
Section: Model Prediction Accuracysupporting
confidence: 86%
“…However, Jian et al experimented with diverse datasets used in deep learning model development studies to compare the prediction accuracy between deep learning, and feature-based ML models. This study showed that the feature-based ML models outperformed the deep learning models in terms of prediction accuracy [17]. Moreover, ML models do not require demanding computation in the training process; therefore, the feature-based ML algorithm is a much more e cient way of developing the model.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations